Finance for the General Management / A Four - Step Approach to the Key Financial Techniques - Mills Roger; Stiles Jan (Mcgraw Hill Book Company, 1994)
Preface, Acknowledgements, Financial Framework for General Management, The Balance Sheet, An Introduction to Profit and Cash Flow, The Relationship Between Financial Statements - Forming a View of the Business, Principles Applied in Preparing Financial Statements, Business Profitability Ratios, Ratios to Measure the Use of Business Assets, Financial Awareness, A Review of Corporate Reports, An Introduction to Analysing Corporate Reports, Analysing Corporate Reports - The Shareholders' and Lenders' Perspectives, The Art of Accounting, Variations in Financial Reporting: The International Dimension, Financial Management: The General Manager as a Financial Manager, Managing Cash, Managing Working Capital, Managing Costs to Support Business Decisions, Managing Capital Expenditure: The Principles, Assessing and Managing Corporate Financial Risk, Financial Direction, Strategic Financial Analysis and Measuring the Value of a Business, The Cost of Capital, Valuation and Business Restructuring.
Preface, Acknowledgements, Financial Framework for General Management, The Balance Sheet, An Introduction to Profit and Cash Flow, The Relationship Between Financial Statements - Forming a View of the Business, Principles Applied in Preparing Financial Statements, Business Profitability Ratios, Ratios to Measure the Use of Business Assets, Financial Awareness, A Review of Corporate Reports, An Introduction to Analysing Corporate Reports, Analysing Corporate Reports - The Shareholders' and Lenders' Perspectives, The Art of Accounting, Variations in Financial Reporting: The International Dimension, Financial Management: The General Manager as a Financial Manager, Managing Cash, Managing Working Capital, Managing Costs to Support Business Decisions, Managing Capital Expenditure: The Principles, Assessing and Managing Corporate Financial Risk, Financial Direction, Strategic Financial Analysis and Measuring the Value of a Business, The Cost of Capital, Valuation and Business Restructuring.